Revision Hip Arthroscopy in the Youth Athlete - Newman, Justin T. (Orthop J Sports Med, 2015)
OBJECTIVES: Despite a dramatic increase in the numbers of primary and revision hip arthroscopy cases that are performed, there is limited literature focusing on the younger population of patients who undergo revision hip arthroscopy. Pathophysiology and post-procedural outcomes of pediatric patients has been demonstrated to differ from adults in many common sports related injuries, including those to the shoulder and knee. The purpose of this study was to describe the indications for and outcomes following revision hip arthroscopy in patients 18 years and younger. Our hypothesis was that these patients would present to revision surgery with different pathology and demonstrate significant improvement in outcomes and return to activity. METHODS: A prospective data registry was queried for all patients 18 years and younger who underwent revision hip arthroscopy with a minimum of 2-year follow-up. Data included detailed surgical data and outcome scores (modified Harris hip (mHHS), Tegner activity scale, and patient satisfaction with outcome) at minimum 2 year follow-up. This study was IRB approved. RESULTS: Thirty hips were included in 29 patients. 24 of the patients were female. Average age at revision was 16.6 (range 15-18). 21 of the patients had one prior surgery, 6 had 2 prior surgeries and 2 had 3 prior surgeries. Mean time from most recent surgery to revision surgery was 18.7 months (range 4.7 to 74 months). Surgeries prior to presentation included 13 with labral debridement, 11 with labral repair, 7 had both cam and pincer addressed, 4 had cam only, 1 had pincer only. 18 patients did not have femoroacetabular impingement (FAI) addressed. 5 patients had iliopsoas releases. At revision, lysis of adhesions was performed on all patients. 12 had labral reconstruction, including 9 of the initial labral debridement patients. 18 underwent cam and pincer resection, including 13 of those without FAI addressed initially. 8 patients had labral repair. 3 patients had iliopsoas release and 1 had iliotibial band release. One patient underwent a periacetabular osteotomy without further arthroscopy. At an average follow-up of 37 months (range 24 to 52 months), the mHHS improved from 57 (25 to 96) to 82 (45 to 96). Mean improvement was 22 points (p<0.001). The median satisfaction was 7 (1 to 10), median Tegner was 5 (1 to 9), SF12 PCS was 50.8 (37.2 to 58.3) and the SF12 MCS was 52.8 (45. to 63.6) CONCLUSION: Revision hip arthroscopy in patients under the age of 18 resulted in good outcomes scores. The majority of these patients were satisfied and all returned to activity. Failure to address FAI and the failure of labral debridement were the most common pathologies precipitating revision hip arthroscopy. This challenging population should be further studied to prevent revision surgery and possible additional irreparable damage.